Enantioselective Total Synthesis of Pseudopteroxazole and Ileabethoxazole. (26th April 2019) - Zhang, Xuan; Fang, Xianhe; Xu, Miao; Lei, Yibo; Wu, Zibo; Hu, Xiangdong
Abstract: Enantioselective total syntheses of pseudopteroxazole (1 ) and ileabethoxazole (2 ) are presented. The two original stereocenters were constructed in excellent enantioselectivity and good diastereoselectivity through Carreira's asymmetric dual catalytic allylation, which shows potential for accessing diastereoisomers at C2 and C3 of 1 and 2 . Cationic cyclizations of 13 and 24 demonstrated an effective pathway for the construction of the opposite configurations at C1 in 1 and 2 . Additionally, an approach for the introduction of methyl at C4 is a feasible solution for structural modifications at C4 in 1 and 2 . Abstract : Anti‐Tuberkulose‐Wirkstoffe : Eine enantioselektive Syntheseroute zu den antimikrobiellen Naturstoffen Pseudopteroxazol und Ileabethoxazol umfasst eine asymmetrische duale katalytische Allylierung, stereoselektive kationische Cyclisierungen, die vermutlich durch π‐π‐Wechselwirkungen kontrolliert werden, sowie eine intramolekulare Friedel‐Crafts‐Reaktion.